Biocontrol Potential of Chitinase-Producing Soil Bacteria Against Fusarium proliferatum - Wulandari Antika Putri; Nisa Rachmania Mubarik; Aris Tri Wahyudi (HAYATI Journal of Biosciences, 2026)
Fusarium proliferatum, a phytopathogenic fungus, causes significant agricultural losses. Chitinase-producing bacteria from post-mining soil have potential as biocontrol agents because they degrade chitin, a major component of fungal cell walls. This study aimed to isolate, characterize, and purify bacterial chitinase and evaluate its antifungal activity against F. proliferatum. Bacterial isolates were obtained from post-mining soil in Martabe and screened for chitinase activity using chitin agar medium. The selected isolates were identified through 16S rRNA gene sequencing, and the chitinase enzyme was partially purified using ammonium sulfate precipitation. The antifungal activity against F. proliferatum was evaluated using dual-culture and food-poisoning assays. Two isolates, TSU4 and TSU5, exhibited high chitinolytic activity with hydrolytic zone indices of 2.1±0.2 cm and 1.9±0.41 cm, respectively; TSU4 (Bacillus cereus) was selected for further study. The 70% ammonium sulfate-precipitated chitinase showed a specific activity of 15.66 U/mg, and the concentrated enzyme inhibited F. proliferatum growth by 33.8±0.23%. Chitinases belong to the glycoside hydrolase family 18 (GH18), an evolutionarily widespread group of chitin-degrading enzymes with a conserved catalytic domain that hydrolyzes β-1,4 linkages in chitin, making GH18 chitinases effective for degrading fungal cell walls in biocontrol applications. These findings indicate that the chitinase produced by B. cereus TSU4 shows significant antifungal activity and has strong potential as a biocontrol agent against F. proliferatum.